Pelatihan Media Digital Interaktif untuk Pembelajaran IPS Sekolah Dasar Berbasis Lingkungan Sosial Siswa - Rani, Afriza Rahma; Rizal, Muhammad Syahrul; Nurmalina, Nurmalina (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to enhance the competence of elementary school teachers in developing and utilizing interactive digital media based on students’ social environments in Social Studies (IPS) learning. The training was carried out using a participatory approach, actively involving partner school teachers in the design, simulation, and evaluation of learning media. Students’ social environment served as the primary source of content to ensure the relevance of Social Studies materials to daily life. The results indicate an improvement in teachers’ understanding of educational technology and their ability to create contextual, creative, and engaging media. This training is expected to support a more meaningful and enjoyable Social Studies learning process for elementary students.